Do cravings predict smoking cessation in smokers calling a national quit line: secondary analyses from a randomised trial for the utility of ‘urges to smoke’ measures - Taggar, Jaspal S; Lewis, Sarah; Docherty, Graeme; Bauld, Linda; McEwen, Andy; Coleman, Tim (BioMed Central, 2015)
BACKGROUND: Single-item urges to smoke measures have been contemplated as important measures of nicotine dependence This study aimed to prospectively determine the relationships between measures of craving to smoke and smoking cessation, and compare their ability to predict cessation with the Heaviness of Smoking Index, an established measure of nicotine dependence.